A IMPLEMENTASI EKONOMI SYARIA'H : MARKETING SYARI'AH: PENGARUH LABELISASI HALAL TERHADAP PEMASARAN PRODUK UMKM DI DESA KUMESU KECAMATAN REBAN KABUPATEN BATANG - Masruri, Masruri (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2025)
This thesis examines the influence of halal labeling on UMKM product marketing. The aim of this research is to find out how halal labeling influences the marketing of UMKM products. The research method used is quantitative correlative research. The sample in this research consisted of 150 respondents. Data collection uses a questionnaire and data processing uses the SPSS analysis tool version 16.020. The research results show that halal labeling has an effect of 45% on the marketing of UMKM products and the remaining 55.% is influenced by other variables.